Institutional Popular Piety: How a Suburban Mosque Produces and Directs Islamic Lifestyle Da'wah in Urban Indonesia - Han, Muhamad Ibtissam; Topikurohman; Sugiarto (FAKULTAS DAKWAH UIN SALATIGA, 2026)
This study examines how Masjid Raya Bintaro Jaya (MRBJ) in suburban Jakarta adapts da'wah to young urban Muslims by integrating health-oriented lifestyles and environmental sustainability. Using a qualitative single-case study design with in-depth interviews with four key informants, supported by observation and document analysis, the study finds that MRBJ operates as a form of institutional popular piety: religious expression is shaped through mosque-initiated programs that draw on middle-class popular culture, rather than market logic. First, MRBJ translates eco-theological concepts into practical mosque programs, including waste donation, biopores, solar panels, greening initiatives, and a reverse vending machine. Second, it mobilizes sport, wellness, and digital activities such as fun runs, health screenings, and online content to attract and engage young Muslims. Third, these initiatives position the mosque as a hybrid institution that combines da'wah, ecological care, and lifestyle-based engagement. The main contribution of this article is theoretical: it extends the concept of popular piety from individual practice and consumer culture to the institutional level, showing that the mosque can actively produce and direct popular piety as a da'wah strategy. These findings enrich scholarship on urban mosques, contemporary da'wah, and popular Islam in Indonesia.